Desempenho, qualidade de ovos e parâmetros intestinais de poedeiras leves alimentadas com rações contendo butirato de sódio protegido - Pires, Marília Ferreira (2016)
The objective of the present study was to evaluate the effect of adding increasing levels of protected sodium butyrate in the diet of laying hens from 61 weeks of age on performance, egg quality and intestinal parameters. The treatments were 0, 105, 210 and 300 g / t of sodium butyrate protected in the feed. To evaluate the performance and quality of eggs, 320 laying hens were used as Dekalb Whyte lineage (61-76 weeks old) in cages and distributed design in blocks (with the weight of the blocky birds), with four treatments and eight replicates of 10 birds. The experiment was 16 weeks divided into four periods of 28 days each. The 76 weeks of age were separated 48 birds for metabolism trial with four treatments and six replicates of two birds. At the end of the assay was sacrificed a repeat per bird for intestinal development analysis. Was conducted analysis of variance and polynomial regression of the data with the help of the statistical program R. Regarding the performance for the period 73-76 weeks of age was negative linear effect for feed conversion (kg feed / kg eggs). For quality variables eggs were observed increasing linear effect for shell thickness in the periods 61-64 and 65-68 weeks and during the periods 69-72 and 73-76 weeks were observed quadratic effect with maximum point 199 and 174 g / t sodium butyrate protected, respectively. For specific gravity quadratic effect was found with a maximum point at 177 g / t sodium butyrate protected only in the period 73-76 weeks. To the percentage of peeling was found quadratic effect on periods 69-72 and 73 to 76 weeks, with a maximum at point 89 and 172 g / t sodium butyrate protected, respectively. To yolk index found a quadratic effect in the period 69-72 weeks of age with a minimum point at 189 g / t of protected sodium butyrate. When evaluating albume index, found a negative linear effect in the period 69-72 weeks of age. For Haugh unit regression was effective only in the period 65-68 weeks with a quadratic effect, with maximum point at 142 g / t of sodium butyrate. In total period was observed quadratic effect for shell thickness, percentage of peel and breakage resistance, in which maximum points were found in 193; 136 and 198 g / t sodium butyrate protected, respectively. When evaluating yolk index in the total period, found a quadratic effect with minimum point at 181 g / t. For intestinal development variables it was found negative linear effect for the length of the jejunum. For height of villi, it found a linear increase in the duodenum and jejunum. For crypt depth, quadratic effect was found in the jejunum with a minimum point at 151 g / t sodium butyrate protected. For the variable villous / crypt ratio was found linear increase in the duodenum and jejunum, and the ileum quadratic effect, with maximum point at 171 g / t. For BN was found quadratic effect with maximum point at 93 g / t, and for BEE was found increasing linear effect. For EMA and EMAn variables were found increasing linear effect. The addition of protected sodium butyrate in laying hens diet did not influence the performance of the birds, but improved the quality of skin and intestinal parameters (intestinal development and metabolization of nutrients). It is recommended to improve the quality of shell eggs in layers in the final production phase, the level of 150 g / t sodium butyrate protected. For intestinal development and diet metabolizable energy level of 300 g / t of sodium butyrate protected.